Cover Image. Issue 1 (22nd January 2019) - Guo, Jiahui; Fang, Liurong; Ye, Xu; Chen, Jiyao; Xu, Shangen; Zhu, Xinyu; Miao, Yimin; Wang, Dang; Xiao, Shaobo
Abstract : The cover image is based on the Original Article Evolutionary and genotypic analyses of global porcine epidemic diarrhea virus strains, by Jiahui Guo et al., DOI 10.1111/tbed.12991 .